Syriac nṣr, Ugaritic nṣr, Hebrew nṣr II, Akkadian nṣr II - Healey, John F.
Syr. nṣr ‘sigh, groan, murmer, howl, etc.’ found in Akk. maṣṣartum ‘lament’ (ARM I 8:14) and nāṣiru (= ikkillu), also in Ugar. (СТА 16 vi 5).